Alterations of Muscle Synergies During Voluntary Arm Reaching Movement in Subacute Stroke Survivors at Different Levels of Impairment - Pan, Bingyu; Sun, Yingfei; Xie, Bin; Huang, Zhipei; Wu, Jiankang; Hou, Jiateng; Liu, Yijun; Huang, Zhen; Zhang, Zhiqiang (Frontiers in Computational Neuroscience, 2018)
Motor system uses muscle synergies as a modular organization to simplify the control of movements. Motor cortical impairments, such as stroke and spinal cord injuries, disrupt the orchestration of the muscle synergies and result in abnormal movements. In this paper, the alterations of muscle synergies in subacute stroke survivors were examined during the voluntary reaching movement. We collected electromyographic (EMG) data from 35 stroke survivors, ranging from Brunnstrom Stage III to VI, and 25 age-matched control subjects. Muscle synergies were extracted from the activity of 7 upper-limb muscles via nonnegative matrix factorization under the criterion of 95% variance accounted for. By comparing the structure of muscle synergies and the similarity of activation coefficients across groups, we can validate the increasing activation of pectoralis major muscle and the decreasing activation of elbow extensor of triceps in stroke groups. Furthermore, the similarity of muscle synergies was significantly correlated with the Brunnstrom Stage (R=0.52, p<0.01). The synergies of stroke survivors at Brunnstrom Stage IV-III gradually diverged from those of control group, but the activation coefficients remained the same after stroke, irrespective of the recovery level.